2014
DOI: 10.1016/j.neuroimage.2013.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Infrared neural stimulation of primary visual cortex in non-human primates

Abstract: Infrared neural stimulation (INS) is an alternative neurostimulation modality that uses pulsed infrared light to evoke spatially precise neural activity that does not require direct contact with neural tissue. With these advantages INS has the potential to increase our understanding of specific neural pathways and impact current diagnostic and therapeutic clinical applications. In order to develop this technique, we investigate the feasibility of INS (λ = 1.875 μm, fiber diameter = 100–400 μm) to activate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
153
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(184 citation statements)
references
References 43 publications
10
153
1
Order By: Relevance
“…This study explored the effects of temperature changes on membrane capacitance and its associated currents in a joint attempt to clarify the experimental results of a key recent study [16] and to pave the way towards predictive modeling of INS [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and other thermal neurostimulation techniques [18][19][20], which could potentially facilitate the development of more advanced and multimodal methods for neural circuit control. Another key motivation to pursue this problem came from our noting the very similar temperature-related capacitance rates of change observed in very different model systems [ Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study explored the effects of temperature changes on membrane capacitance and its associated currents in a joint attempt to clarify the experimental results of a key recent study [16] and to pave the way towards predictive modeling of INS [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and other thermal neurostimulation techniques [18][19][20], which could potentially facilitate the development of more advanced and multimodal methods for neural circuit control. Another key motivation to pursue this problem came from our noting the very similar temperature-related capacitance rates of change observed in very different model systems [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Both approaches also offer the long-term prospect of remotely affecting aberrant localized neural circuits that underlie many neurological diseases. A multitude of INS-related studies explored the ability of short-wave infrared (IR) pulses to stimulate neural structures including peripheral [3,4] and cranial nerves [5][6][7][8][9][10], retinal and cortical neurons [10][11][12], as well as cardiomyocytes [13,14]. It is stipulated that the INS phenomenon is mediated by temperature transients induced by IR absorption [15][16][17]; such transients can alternatively be induced using other forms of photoabsorption [18][19][20], or potentially by any other physical form of thermal neurostimulation that can be driven rapidly enough [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…These include the time and cost required to perform genetic manipulations, the potential that the added ion channels may alter the electrical properties of the cells, the decreased responsiveness to light with repeated stimulation [38], and the likelihood of triggering an action potential when the light-sensitive channels are exposed to the optical mapping excitation light due to overlap of the excitation spectra [39,40] and much lower power requirements necessary for exciting the channels [41]. Infrared stimulation does have the potential to damage tissue if too much heat is deposited, but previously published results suggest that infrared stimulation can be used without damage [24][25][26][27][28][29][30][33][34][35]. Similarly, in this study, no functional damage was observed, as the pacing threshold did not increase over the course of an experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Infrared stimulation was first developed in nerves [24] and has been used to stimulate a variety of nerves and neurons [25][26][27][28][29][30], vestibular hair cells [31], and isolated myocytes [32] using multimode fibers. Additionally, we have recently demonstrated the use of infrared stimulation to optically pace whole intact embryonic [33] and adult hearts [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation